The effect of dietary apigenin on colonic ornithine decarboxylase activity, aberrant crypt foci formation and tumorigenesis in different experimental models - Au, Angela; Li, Boyong; Wang, Weiqun; Roy, Hemant; Koehler, Ken; Birt, Diane (My University, 2006)
The efficacy of dietary apigenin, a dietary flavonoid, in colon cancer prevention was investigated by evaluating the inhibition of the ornithine decarboxylase (ODC) activity and the formation of aberrant crypt foci (ACF) and by studying the ability of apigenin to block colon carcinogenesis in two mouse models. First, the activity of ODC was measured in colon cancer cells (Caco-2) and in the colon epithelium of CF-1 mice. Apigenin at 10 and 30 μM significantly inhibited the ODC activity of Caco-2 cells by 26 and 57% respectively. Colonic ODC activity in CF-1 mice was reduced with 0.1% dietary apigenin by 42% compared with the control but this difference was not statistically significant. Second, ACF formation was evaluated in azoxymethane (AOM)-induced CF-1 mice. Female CF-1 mice at 6 weeks of age were i.p. injected with 5 mg/kg body weight (BW) AOM once to induce ACF. ACF formation in CF-1 mice was reduced by 50% (p<0.05) with 0.1% dietary apigenin fed for 6 weeks when compared with the control. Dietary apigenin inhibited ACF only in the distal region of the CF-1 mouse colon. Finally, tumorigenesis studies were conducted using two different mouse models: AOM-induced CF-1 mice and Min mice with mutant adenomatous polyposis coli (APC) gene. Female CF-1 mice at 6 weeks of age were i.p. injected with 10 mg/kg BW AOM weekly for 6 (AOM Study I) or 4 (AOM Study II) weeks to induce tumors. CF-1 mice were fed diets containing 0.025 or 0.1% apigenin for 23-25 weeks. Female Min mice were fed diets for 10 weeks beginning at 5 weeks of age. In two AOM-treated mouse colon tumor studies 0.025% and 0.1% dietary apigenin modestly reduced tumors in the group fed 0.025% apigenin (25% incidence in comparison with 65% in the controls) in a non-dose response manner. Apigenin failed to inhibit adenoma formation in the Min mouse study. These results suggest that dietary apigenin showed promise in cancer prevention by reducing the ODC activity and ACF formation, however, clear evidence of cancer prevention was not obtained in mouse tumor studies. Further investigation of the potential chemopreventive effect of apigenin in carcinogenesis is warranted.
Keywords: Apigenin; Colon cancer